Evaluating the therapeutic potential of Wolbachia in controlling mosquito-borne diseases: a systematic review and meta-analysis - Mohamad Javier, R.; Arlond, Faisal Gani Putra; Putra, Dwi Permana; Prathama, Christopher Bryant; Wardhana, Gede Raditya Wisnu; Tansuri, Verika Christabela; Prasetya, Adrian; Ramadhan, Fadli; Hanum, Aisyah Rizki Nirmala; Fitriasa, Rayyan; Izzati, Maulidi; Nabila, Putri; et al. (Frontiers in Tropical Diseases, 2025)
IntroductionWolbachia, an endosymbiotic bacterium, has been the subject of intensive research due to its potential as a macrofilaricidal and microfilaricidal agent, especially in the control of diseases transmitted by mosquitoes, such as Dengue Hemorrhagic Fever (DHF), Cardiac Dirofilariasis, and Tropical Pulmonary Eosinophilia (TPE). In addition, associations with phenomena such as Creeping Eruption and Intraocular Filariasis are also the focus of attention.ObjectiveThis study aims to systematically evaluate the clinical and entomological outcomes of Wolbachia mosquito vector therapy on DHF, Cardiac Dirofilariasis, and TPE, while also assessing associated symptoms across different age groups.MethodsA systematic review and meta-analysis were conducted by searching PubMed, ScienceDirect, Cochrane Library, Embase, and Scopus for original research, systematic reviews, and meta-analyses published in the last five years. Included studies comprised clinical trials and observational designs (cohort and case-control). Thirteen eligible studies were analyzed, including four randomized clinical trials, seven observational studies, one systematic review, and one guideline. Data were extracted independently by three reviewers, and outcomes were synthesized narratively and quantitatively using GRADEpro software, with effect sizes presented as risk ratios (RR) and 95% confidence intervals (CI).ResultsWolbachia deployment in Aedes aegypti significantly reduced DHF incidence by 77.1% and hospitalization rates by 86.2%. In cardiac dirofilariasis, Wolbachia’s surface protein (rWSP) modulated angiogenesis by increasing VEGF-A and lowering anti-angiogenic sEndoglin levels. Environmental analyses indicated a microfilaricidal effect in areas with ≥20% wMel prevalence. Wolbachia’s spread is influenced by host biology, demographic, and ecological factors. All key findings were rated as moderate certainty (GRADE: B) meaning the true effect is likely close to the estimate, but further research could change this.ConclusionWolbachia vector therapy shows promising macrofilaricidal and microfilaricidal properties across multiple mosquito-borne diseases, with moderate-quality evidence supporting its role in reducing transmission and disease burden.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier PROSPERO (CRD420251016056).